Perbedaan Pengetahuan, Sikap dan Perilaku Hygiene Sanitasi Makanan Dengan Kejadian Kesakitan pada Remaja Putri dan Penjamah Makanan di Pondok Pesantren Komplek Al-Fuadiyah Nurul Huda Kabupaten Pringsewu Tahun 2024 - Susanti, Nurul; Jayadi, Ajib; Nurhartanto, Adhi (Journal of Education Technology Information Social Sciences and Health, 2025)
Background: Health and well-being are the most important aspects of an individual, especially for adolescent students in Islamic boarding schools. Food sanitation hygiene is also important for every human being to know, especially for food handlers who provide food in an institution. The results of the World Healt Organization (WHO) 2019 diarrhea is an environmentally based disease and occurs in almost all geographical areas in the world, every year there are around 1.7 billion cases of diarrhea with a death rate of 760,000. Purpose: This study aims to determine differences in knowledge, attitudes and behavior of food sanitation hygiene with the incidence of illness in adolescent girls and food handlers at the Al-Fuadiyah Nurul Huda Pringsewu Islamic Boarding School complex. Methods: The type of research conducted was quantitative with a cross sectional approach. This study used random sampling technique involving a sample of 60 respondents who were at the Al-Fuadiyah Nurul Huda Pringsewu Islamic Boarding School. Results: In this study, statistical tests with cross sectional between differences, attitudes and behavior with the incidence of morbidity obtained an average p-value (0.05) while the difference between knowledge, attitudes and behavior with the incidence of morbidity obtained a knowledge p-value (0.898) attitude p-value (0.361) behavior p-value (0.666). Conclusion: This study shows that there is no significant difference between knowledge, attitudes and behavior with the incidence of morbidity at the Nurul Huda Al-Fuadiyah Islamic Boarding School with the results of p-value (0.05).